Recurrent Narratives Around the COVID-19 Crisis in Social Networks: A Case Study Analysis on Facebook - Papa, Venetia; Maniou, Theodora A. (My University, 2020)
In recent years, social networks have played a significant role during major crisis events as citizens use these networks to seek information, discuss and share personal news stories, while interacting with other users regarding issues related to the perceived crisis. As a result, news content posted on social networks is of crucial importance since it can affect public opinion in various ways. The aim of this study is to assess dominant narratives generated through users’ reactions towards news content posted on Facebook so as to examine the role of Facebook during the global crisis of COVID-19. Drawing from different aspects of crisis communication theory and audience-centered studies, this work seeks to investigate the constructed meanings related to this crisis and interpret users’ understanding of news content posted on social networks. Content analysis is employed as a means to evaluate Facebook’s potential in (re)defining users’ narratives regarding issues related to COVID-19.
Keywords: COVID-19; Facebook; Crisis, users’ narratives; News stories